The use of picture card media on the reading ability of elementary school students - Maria Veronika Gleko; Desi Maria El Puang; Frederiksen Novenrius Sini Timba (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
Some grade 1 students of SD Inpres Nogodue have not been able to read properly and correctly. It is known that out of 22 students, there are 9 students whose ability to recognize letters is still low. Of these 9 students, 3 students were able to recognize letters but still could not distinguish letters such as the letters n and m, j and i, t and f, b and d, a and e, g and p, z and y. 1 student has been able to recognize letters but has not been able to write them, and 5 students have not been able to recognize letters at all. In addition, there are still most students who have not been able to recognize punctuation. The solution taken to overcome this problem is by using picture letter card media. The research design used was a one group pretest posttest design. The sample in this study amounted to 22 people. Data collection techniques used tests and observations with research instruments in the form of test questions and observation sheets, and data analysis techniques used the normality test with the Kolmogorov Smirnov test and hypothesis testing using the t-test. Research result,obtained a significance value (2-tailed) of 0.000 ? 0.05, then accept Ha and reject Ho. Thus, the conclusion is that "there is an effect of the use of illustrated letter card learning media on the reading ability of grade I students at SD Inpres Nogodue.